“Influencia del ácido -3- indol butírico y tipo de sustrato en el enraizamiento de plukenetia carolís- vegae en la povincia de San Martín-Perú” - Paredes Del Aguila, Patricia (2016)
This reseªrch ªims specificªJJy tº determine the highest ªºº best effect .of rooting Plukenetia carolis-vegae (Bussmann et al., 2013), through four doses of acid indole- 3-butyric and two types of substrates chªmbers sub irrigªtiQn in th~ proving3 Qf ~n Martin. This research was conducted at the premises of the Research lnstitute of the Peruvian Amazon llAP ,. S~m f\,11artin, 19_c~t~<;f ir:i .th.~ <;f lstricCt Qf MC?:r~J~~. prq.yJn~~ .~n.d department of San Martin; UTM coordinates of which they are N 9283654 and 9~4774~ E and at an altitude of 3.32 m.s.n.m.m. Far the implementation of this research design was completely randomized factorial arrangement 4 x 2 (4 doses of AIB and 2 types of suhstrate) with 3 replications and 12 cuttings per experimen~.1 unit. The results obtained in the field were processed using the statistical program insfostat. Data were analyzed using analysis of variance and subjected to the Tukey test with a significance level (p <0.05) probability of error in determining the nature of the cüfferences between treatments. Previous analysis, data rooting percentage, number of roots, percentage of sprouting, were transformed by arcsin formula and processed data count (Snedecor and Cochran 1980). (Pampa Hermosa) - Stakes kind of Plukenetia carolis-vegae (Bussmann et al, 2013), which were collected in the region of Amazonas province Rodríguez de Mendoza, limahamha District were used. The variables evaluated were: percentage of rooting, number of roots, root length and greater percentage of sprouting. The results indicate that the best dese of acid indole-3-butyric rooting juvenile cuttings in Plukenetia carolis-vegae, was 0.6% of AlB, compared to other doses of AlB. The type of substrate with the best results was fine for rooting juvenile cuttings in Plukenetia carolis-vegae gravel. Keywords: Plukenetia carolis-vegae) influence) acid, butyric indoJe, dosage) substrate, fine gravel, half sand, sprouting, roots, percentage, rooting.